ONLINE LEARNING AND SOCIAL INTERACTION OF STUDENTS FROM RURAL FAMILIES (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
The Covid-19 pandemic has made learning switch from face-to-face to online. This situation makes it possible for teachers and students to interact still and discuss online, using existing internet applications such as Whatsapp groups, Instagram lives, Zoom meetings, Google meet, and others. This study explores student interactions during online learning and describes how students feel while studying from home, especially in the rural milieu. Using a phenomenological approach, the researcher describes the phenomenon and reality from the subject's experience. The results showed that most elementary school students used their parents' cellphones so that social interaction between them was still intertwined. This nuance differs from junior and senior high school students who, on average, already have their device facilities, so they are not too dependent on their parents. The impact of this independence is the low level of social interaction between junior and senior high school students and their parents. However, the senior high school students stated that they tend to learn how to use social media to sell goods and connect with other people from different cultures. Socially, they also have new friends due to connecting with social media, even though, in reality, they are living in the countryside, with all its limitations. To cite this article (7th APA style): Yusnita, T., Adeni, S., & Harahap, M. A. (2022). Online learning and social interaction of students from rural famiies. Journal Communication Spectrum: Capturing New Perspectives in Communication 12(2), 146-154. https://doi.org/10.36782/jcs.v12i2.2235